Survey of rehabilitation support for children 0-15 years in a rural part of Kenya. - Bunning, K; Gona, J; Odera-Mung'ala, V; Newton, C; Geere, J; Hong, C; Hartley, S (Informa Healthcare, 2014)
PURPOSE: Information regarding the nature, availability and distribution of rehabilitation services for children with disabilities across developing countries is scarce, and data that do exist are of variable quality. If planning and development are to progress, information about service provision is vital. The aim was to establish the scope and nature of rehabilitation support available to children with disabilities (0-15 years) and their families in rural Kenya. METHOD: A comprehensive sample comprising service provision in the health and special education sectors was established. Non-governmental and community-based organisations were also included. A survey of rehabilitation services was conducted through examination of service-related documentation and key informant interviews with the heads of services. RESULTS: Rehabilitation comprised hospital-based occupational therapy, physiotherapy and orthopaedic technology; and seven special education establishments plus an education assessment resource centre. There was one non-government organisation and one community-based organisation relevant to children with disabilities. Activities focused on assessment, diagnosis and raising community awareness. Provision was challenged by inadequate staffing, resources and transport. Government funding was supplemented variously by donations and self-sufficiency initiatives. Rehabilitation approaches appeared to be informed by professional background of practitioner, rather than the needs of child. Service documentation revealed use of inconsistent recording methods. CONCLUSIONS: The data highlight the challenges of rehabilitation, demanding greater investment in personnel and their training, more material resources, improved access to the community and better recording mechanisms. IMPLICATIONS FOR REHABILITATION: There needs to be greater investment in rehabilitation provision in developing countries. Consideration of community-based initiatives is required to support better access for all. In order to argue the case for improved resources, better skills and mechanisms for recording, monitoring and evaluating practice are needed.